The cognitive observer-based landmark-preference model : what is the ideal landmark position at an intersection? - Röser, Florian; Justus Liebig University Giessen (My University, 2015)
Which object at an intersection is the ideal landmark for humans? Why one object and not other? These are the central questions in the exploration of human wayfinding processes, and they are thus part of spatial cognition research. The research literature so far provides quite a few concepts and approaches for how these landmarks should be classified and how the single factors the saliences influence the landmark preferences during wayfinding. This Dissertation follows this approach and presents a systematic variation of the saliences. I investigated the influence of the position, the color, and the shape of the landmark and further examined whether landmark preference depends on the observer´s point of view and viewing direction. The features of an object, the relationship between the present objects, the relationship between the object and the environment, and the relationship between observer and object will be considered. A series of experiments in which participants were asked concerning their landmark preference for providing route directions revealed the following: First, the color of the potential landmark must contrast with the object colors in the environment in order to be preferred this is the visual salience. Second, the ideal landmark position is before the intersection in the direction of the turn this is the structural salience (allocentric perspective). When both saliences compete with each other, participants consider both aspects to different amounts. Third, the results reveal that the structural and the structural-visual effects in an egocentric perspective are influenced by the viewpoint-based salience. All relevant saliences are integrated into a landmark-preference model. The comparison of a mathematical abstraction from this model reveals a good fit with empirical results. These findings are discussed with respect to the current literature and other models and their relevance for everyday wayfinding.

Welches Objekt an einer Kreuzung ist die ideale Landmarke für einen Menschen? Warum dieses Objekt und nicht ein anderes? Dies sind die zentralen Fragen bei der Erforschung der Prozesse beim menschlichen Wegfinden und ist damit dem Gebiet der Raumkognition zuzuordnen. Die Forschungsliteratur hat bisher einige Konzepte und Ansätze präsentiert, wie diese Landmarken zu klassifizieren sind und wie diese einzelnen Faktoren die Salienzen die Präferenzentscheidung von Landmarken beim Wegfinden beeinflussen. Die vorliegende Arbeit folgt diesem Ansatz und präsentiert eine systematische Variation der bedeutsamen Faktoren. Untersucht wird, welchen Einfluss die Position einer Landmarke, deren Farbe und Form sowie der Blickpunkt des Beobachters auf die Wahl der idealen Landmarke hat. Dabei werden sowohl die Eigenschaften des Objektes, als auch die Beziehungen der Objekte untereinander, die Beziehung des Objektes zur Umgebung und die Beziehung zwischen dem Beobachter und dem Objekt berücksichtigt. Eine Serie von Experimenten in welchen gefragt wurde, welche Landmarken man präferieren würde, um eine Wegbeschreibung zu geben, erbrachten Folgendes: Erstens muss sich die Landmarke farblich deutlich von der Umgebung abheben um präferiert zu werden dies ist die visuelle Salienz. Zweitens ist die ideale Landmarkenposition vor der Kreuzung und in Abbiegerichtung dies ist die strukturelle Salienz (allozentrische Perspektive). Wenn diese beiden Salienzen miteinander konkurrieren, berücksichtigen die Probanden beide Aspekte bei ihrer Landmarkenpräferenz. Drittens konnte gezeigt werden, dass die strukturellen und strukturell-visuellen Effekte in einer egozentrischen Perspektive durch die blickpunktabhängige Salienz beeinflusst werden. Alle relevanten Salienzen werden zu einem Landmarkenpräferenzmodell zusammengefasst. Ein Vergleich der mathematischen Ableitung aus diesem Modell zeigt eine sehr gute Passung mit den empirischen Befunden. Diese Befunde werden unter Berücksichtigung der relevanten Literatur sowie anderer Modelle diskutiert und die Relevanz für den alltäglichen Gebrauch wird aufgezeigt.
Das kognitive beobachterzentrierte Landmarkenpräferenz Modell : Was ist die ideale Landmarkenposition an einer Kreuzung?
Keywords: psychology; cognition; spatial cognition; wayfinding; landmark; ddc:150